Pengaruh Performance Expectancy dan Effort Expectancy Terhadap Pengguna Mobile Banking - Alfattaah, Muhammad Syahid; Situngkir, Tiar Lina (Peneliti.net, 2024)
Mandiri mobile banking application from PT Bank Mandiri Tbk is a financial application. Bank Mandiri customers can print bank statements, validate transactions, access other financial platforms, and make withdrawals effectively. In addition, customers can also view transaction pages effectively. This study aims as an effort to determine the effect of performance expectations, effort expectations and behavioral intentions related to the behavior of using Mandiri banking services in Karawang. For this study, 110 respondents of Mandiri mobile bank customers in Karawang who could not be identified were used. The research method was carried out with path analysis. The results show that behavioral intention has a positive but insignificant effect on the performance expectation variable, by having a calculated t value of 1.742> t table (0.187) with a significant value of 0.085> 0.05. Effort expectations on behavioral intentions are positively and significantly correlated with behavioral intentions with a t value of (4.053) > t table (0.187) and a significance level of 0.000 <0.05. Behavioral intention has a significant and somewhat positive influence on user behavior, which is indicated by the sig value of 0.001 < 0.05 and t count (3.455) > t table (0.187).